2019
DOI: 10.3390/photonics6020056
|View full text |Cite
|
Sign up to set email alerts
|

Propagation of Cylindrical Vector Laser Beams in Turbid Tissue-Like Scattering Media

Abstract: We explore the propagation of the cylindrical vector beams (CVB) in turbid tissue-like scattering medium in comparison with the conventional Gaussian laser beam. The study of propagation of CVB and Gaussian laser beams in the medium is performed utilizing the unified electric field Monte Carlo model. The implemented Monte Carlo model is a part of a generalized on-line computational tool and utilizes parallel computing, executed on the NVIDIA Graphics Processing Units (GPUs) supporting Compute Unified Device Ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 51 publications
0
18
0
Order By: Relevance
“…In recent years, the connection between attenuation and OAM has been investigated in the context of biology and medicine 7,8,13,[19][20][21] . Studies that have used numerical methods that model this problem have shown that increasing the topological charge does improve permeability and increases the contrast of the outgoing beam [22][23][24] . These results were consistent with results of other experiments on OAM transmission 22 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, the connection between attenuation and OAM has been investigated in the context of biology and medicine 7,8,13,[19][20][21] . Studies that have used numerical methods that model this problem have shown that increasing the topological charge does improve permeability and increases the contrast of the outgoing beam [22][23][24] . These results were consistent with results of other experiments on OAM transmission 22 .…”
mentioning
confidence: 99%
“…Studies that have used numerical methods that model this problem have shown that increasing the topological charge does improve permeability and increases the contrast of the outgoing beam [22][23][24] . These results were consistent with results of other experiments on OAM transmission 22 . In this work, we use relatively thicker biological tissue, reaching the cm range.…”
mentioning
confidence: 99%
“…The variety of these vectors does depend upon the anisotropy of the medium, giving useful insight towards the detection and grading of cervical precancer. There are some reports that employ the use of complex vector beams for diagnosis purpose. These beams are independent of the anisotropy of the medium and can unify the currently available polarimetry.…”
Section: Resultsmentioning
confidence: 99%
“…In a continuation of previous research, in [66] using Monte-Carlo simulation with GPU CUDA the propagation of cylindrical vector beams (CVB) in turbid tissuelike scattering media was explored in comparison with conventional Gaussian laser beams. The authors also pioneered the application of MC for imitation of the propagation of vector light beams in turbid media.…”
Section: Polarimetry and Mueller Matrix Measurementmentioning
confidence: 99%